Eksplorasi Pengaruh Interaksi Sosial di Lingkungan Sekolah terhadap Perkembangan Emosional Siswa Kelas V Sekolah Dasar 060875 - Dea Fitri Ananda Sormin; Anggun Trianisyah Juli; Nelly Trioctavia Manik; Syahrial Syahrial (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study explores the influence of social interactions in the school environment on the emotional development of fifth-grade students at SDN 060875 Medan. Using an explanatory sequential mixed-methods design (30 participants), data were collected through participatory observation, emotional intelligence scales (EIK), and interviews. Results revealed a significant positive correlation between social interaction and emotional regulation (r = 0.62; p < 0.05). Cooperative interactions (65% of total interactions) and partner diversity were critical for developing empathy and self-awareness. Teachers functioned as emotional models through emotion coaching techniques, while a mastery goal-oriented classroom climate strengthened this relationship. Practical implications include integrating social-emotional learning (SEL) into cross-group collaborative activities and structured peer mentoring programs. This research affirms social interaction as a constitutive foundation for emotional development in Indonesia’s socio-cultural context.